2020
DOI: 10.3389/fphar.2020.580407
|View full text |Cite
|
Sign up to set email alerts
|

CC-223, NSC781406, and BGT226 Exerts a Cytotoxic Effect Against Pancreatic Cancer Cells via mTOR Signaling

Abstract: The mTOR signaling pathway is abnormally activated in pancreatic cancer and is related to tumor glucose metabolism. However, its specific regulation mechanism is still unclear. Therefore, this study aims to investigate whether Sestrin2 affects the glucose metabolism of pancreatic cancer by modulating mTOR signal and then affects its biological behavior. We have observed that l-leucine can promote the proliferation of pancreatic cancer cells and increase the expression of Sestrin2 and p-mTOR proteins. In order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Onatasertib (CC-223, DB12570) is an orally available, low nanomolar inhibitor of mTOR (IC 50 = 10 nM) [ 156 ], with putative antineoplastic activity [ 133 , 157 , 158 ]. The inhibition of mTOR by Onatasertib has been reported to induce tumor cell apoptosis and to decrease tumor cell proliferation [ 124 , 159 , 160 , 161 ]. Onatasertib is currently in phase II trials for the treatment of multiple myeloma, non-Hodgkin’s lymphoma ( ID: NCT01177397), and hepatocellular carcinoma ( ID: NCT03591965) and is in phase I trials for non-small-cell lung cancer ( ID: NCT01545947).…”
Section: Resultsmentioning
confidence: 99%
“…Onatasertib (CC-223, DB12570) is an orally available, low nanomolar inhibitor of mTOR (IC 50 = 10 nM) [ 156 ], with putative antineoplastic activity [ 133 , 157 , 158 ]. The inhibition of mTOR by Onatasertib has been reported to induce tumor cell apoptosis and to decrease tumor cell proliferation [ 124 , 159 , 160 , 161 ]. Onatasertib is currently in phase II trials for the treatment of multiple myeloma, non-Hodgkin’s lymphoma ( ID: NCT01177397), and hepatocellular carcinoma ( ID: NCT03591965) and is in phase I trials for non-small-cell lung cancer ( ID: NCT01545947).…”
Section: Resultsmentioning
confidence: 99%
“…and plays a significant role in the tumorigenesis of pancreatic carcinoma [ 36 ]. It is abnormally activated in pancreatic cancer and is related to tumor glycolysis (Warburg effect) and other glucose metabolism process [ 37 ]. In addition, the mTOR signaling pathway also promotes gemcitabine resistance in PC.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the knockdown of sestrin 2 inhibited the growth of pancreatic cancer in vivo. This latter study indicated that the mTOR signaling pathway participated in sestrin 2-mediated promotion and development of pancreatic cancer [ 82 ].…”
Section: Promotive Effects Of Sestrin 2 In Cancermentioning
confidence: 99%